Five Visual and Olfactory Target Genes for RNAi in Agrilus Planipennis - Fan, Zhizhi; Zhang, Zhen; Zhang, Xun; Kong, Xiangbo; Liu, Fu; Zhang, Sufang (Frontiers in Genetics, 2022)
RNA interference (RNAi) is a widely used technique for gene function research and recently pest controls. It had been applied in larvae and adults emerald ash borer (EAB), Agrilus planipennis, achieving significant interference effects, whether by ingesting or microinjecting. Feeding in the phloem and cambial regions, the larvae of A. planipennis are difficult to be touched and killed by conventional insecticides, so adult stage is the critical stage for EAB control. However, the target genes of adult stage of A. planipennis need to be further screened. Here, we preliminarily screened 5 potential target genes of vision and olfaction for RNAi in A.planipennis. Three odorant-binding proteins (OBPs) and three opsins, which expressed significantly different between newly emerged and sexually mature EABs (OBP5, OBP7, OBP10, LW opsin 1 and UV opsin 2) or highly in sexually mature male EAB (UV opsin 3), were selected as targets to design primers for gene silencing. After dsRNA injection, the gene expression levels were determined by real-time quantitative PCR. We found the expression levels of 5 genes were significantly down-regulated, during the 4 days after dsRNA injection. Among these genes, the expression of LW opsin 1 was down-regulated the most, causing a reduction of 99.1% compared with the control GFP dsRNA, followed by UV opsin 3 (97.4%), UV opsin 2 (97.0%), OBP7 (96.2%), and OBP10 (88.7%). This study provides a basis for further RNAi-based new controlling method development of A.planipennis at adult stage.